How Do You Like Me Now? The Influence of "Likes" and Followers on Social Media in Plastic Surgery. Issue 4 (23rd February 2022) - Bhat, Deepa; Kollu, Tejas; Ricci, Joseph A.; Patel, Ashit
Abstract : Background: The number of "likes" and followers on social media is a surrogate marker for peer acceptance and popularity, but the influence of likes and followers on prospective plastic surgery patients has not been studied. The aim of this study was to evaluate whether the number of followers or likes on social media has an impact on perceived surgeon competence or likelihood of recruiting new patients. Methods: A fictitious Instagram page was created with different permutations displaying different numbers of followers on the page. Similarly, fictitious Instagram posts were created displaying before-and-after results of ideal and suboptimal breast augmentation and gynecomastia surgery results, with the number of likes being the only variable. Using a crowdsourcing platform, survey responders rated surgeon competence and likelihood of patient recruitment based on the Instagram post. Results: A total of 4284 responses were collected. The number of followers or likes did not impact perceived surgeon competence or patient recruitment scores. Optimal surgical results consistently scored higher than suboptimal results, regardless of the number of likes. Almost half the responders were unable to identify the American Board of Plastic Surgery as the appropriate board certification for performing aesthetic breast or body surgery. Conclusions: A high number of followers or likes, by itself, is unlikely to translate into higher likelihood of recruiting new patients. Overall, aesthetic results seem to be the most important driving force in receiving high competence scores and recruiting new patients, rather than social media presence or board certification.